Mesin Pencetak Stik Bentuk Akar Kelapa - Zaldy Kurniawan; Hariyanto Hariyanto; Findra Setyanto; Rapiansah Rapiansah; Zulkipli Zulkipli (Politeknik Manufaktur Negeri Bangka Belitung, 2016)
Besides getas and kemplang, one snack which most people like in Bangka Island isa a snack with the form of a palm tree roots. The craftsmen who manufacture these sticks derived from Pangkalpinang. The results of the survey on the Small Industries (IKM) in the District Gerunggang show that the production process sticks using manual equipment/manpower. To overcome the problems of IKM, hence the researcher designed to facilitate the molding machine in the production process and speed up production so as to produce a better capacity of production by using the manual method. The method used in this research is to design and calculation by using computing devices Solidwork. This stick molding machine uses a mechanism that rotates a threaded shaft, then an emphasis on the dough so that these products can be pushed toward the output. From the experimental results the output of this machine is the root of the stick-shaped palm with a size 100x5 mm, output 500 gram / 5 minutes by the number of ± 80-100 grains stick.